Analysis of the Contact Dynamics Characteristic of Cylindrical Gear with Arcuate Tooth Trace - Qing Xin; Hou Li; Ma Dengqiu; Wang Hong (Jixie chuandong)
Based the UG,the three- dimensional models of different tooth width of cylindrical gears with arcuate tooth trace are established.The change rule of rotational speed and meshing forces are obtained through comparing and analyzing the kinematics and dynamics of different tooth width by help of ADAMS.By the kinematics analysis,the running steadiness of cylindrical gear with arcuate tooth trace is verified.When 1.3r0<b<1.9r0,the error of rotation speed is the smallest.By dynamics analysis,when 1.2r0<b<1.8r0,the gear pair has the best transmission stability,load capacity and the best performance.Therefore,the theoretical basis for the design of cylindrical gears with arcuate tooth trace under the high speed and heavy load condition is provided by this analysis method and has engineering applications value.